Perancangan Surat Keterangan Kerja Berpengaman Berbasis Web Dengan Metode Prototype Pada PT. Hartono Istana Teknologi - Dewanta, Laurentius Ruiz Yakhrisma; Rudianto, Christ (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
PT. Hartono has a problem with making a work certificate where the letter requires a signature from the leadership, and if the leader is not present there will be a delay. This research aims to design a website-based information system to assist in the process of submitting, producing work certificates required by employees, and validating letter by company leader. This research uses a qualitative method that uses the figma application to make the design and with a prototype method approach. With this design, it will produce a web-based information system that can assist the process of submitting and making work certificates for employees at PT. Hartono